CONTRIBUIÇÕES DA RESOLUÇÃO DE PROBLEMAS E DO SOFTWARE MAPLE PARA A APRENDIZAGEM SIGNIFICATIVA DOS CONCEITOS E PROPRIEDADES DA DERIVADA - Sangoi, Elio (2010)
The central theme of this paper is to analyze the contributions of problem solving and software maple in the understanding and comprehension of concepts and properties of the derivative, with the anchors the cognitive theory of Ausubel (1989, apud Moreira). With this vision, we tried to find new paths through the resolution of problems to study in a class of Derivative Calculus A Course of Engineering, to improve educational action from the construction of new knowledge. From this perspective, learning takes place through meanings. We adopted a qualitative methodology and data collection was used observations and questionnaires to assess how students learn for meaning, to solve problem situations involving the study of Derivatives. The identification of these procedures allowed the teacher to see how students were processing their knowledge, thus giving subsidies to plan teaching practice. By analyzing the collected data with the theoretical foundation of meaningful learning, the study of Derivative gained new meaning to be proposed by resolution of problems. By analyzing the situations, problems with the use of maple software coupled with the theoretical foundation, it was possible to understand that this teaching strategy has given new meaning to the calculation for the students, therefore, appreciated the work of mind, their prior knowledge and their efforts. With the identification of evidence of meaningful learning, it was possible an understanding of how students internalize new knowledge. As evidence of the results of meetings held during the lessons and complemented by the observation form and questionnaires, it can be inferred that the results in percentage terms, indicate a recovery between 80 and 97 per cent. Using software maple, about 100 percent of the students considered that it was valid to their learning.